Filsafat Positivisme Auguste Comte: Perdebatan Pemikiran dan Keberadaan Agama Positif - Hudri, Misbah (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
Positivism as a philosophical movement has played a crucial role in the development of modern philosophy. Its existence marks a significant point in the discourse of philosophical scholarship. Essentially, this philosophical movement is quite old, known long before it was introduced by the figures discussed in this writing. The discussion in this writing aims to convey information about positivism in the style of Auguste Comte. In connection with the debates surrounding his thoughts, criticisms, or the search for positive aspects of positivism itself, it is important to note. Beyond that, an important aspect to be discussed is also related to the positive religion commonly known as